Unjuk Kerja Kolektor Pemanas Air Tenaga Surya Sistem Termosifon Dengan Pemanfaatan Kaleng Minuman Bekas Sebagai Adsorber - Gihon Matondang; Azridjal Aziz; Rahmat Iman Mainil (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The beverage cans is one of waste due to human activities. Most of the used beverage cans that can be found in a neighborhood were made of aluminum. Beverage cans at nowadays is often recycled become useful goods. Solar energy is the energy form of light and heat of the sun. solar energy in active used by solar water heater. In the solar water heater, there care collectors that can be used to absorb the sun's heat energy that is usually made of aluminum. This study aims to take advantage of used beverage cans as a collector and a test to determine the ability of the tool to heat the water. Solar water heater has the dimensions of length 2.3 m, width 0.87 m, a height of 1.5 m, and a volume of 127 L. The results reveal that highest temperature of the absorber obtained by 71,1 oC at 12:30 pm. The raising temperature of water in the tank from the initial temperature 28,3oC up to 43,30C.Keywords: Beverage cans, Solar Water Heaters, Collector.